Penile Preservation in a Young Adult with Aggressive Spindle Cell Carcinoma: A Case of Wide Local Excision and Glanular Reconstruction in a Resource-Limited Setting - Dony Marthen Bani; Syaeful Agung Wibowo (HM Publisher, 2026)
Penile sarcomatoid squamous cell carcinoma, also known as spindle cell carcinoma, is a rare and aggressive malignancy characterized by biphasic histology. Its management in young adults under 40 years of age is challenging, particularly in resource-limited settings where advanced diagnostic adjuncts like immunohistochemistry are often unavailable, necessitating reliance on morphological diagnosis and clinical acumen. We report the case of a 36-year-old uncircumcised male presenting with a rapidly growing, 2.5 cm exophytic glanular mass (cT2N0M0). Diagnostic workup relied on clinical assessment and morphological evaluation to rule out differentials, as immunohistochemical markers were unavailable. The patient underwent penile-sparing wide local excision (WLE) with intraoperative frozen section control (5 mm margins) and primary glanular reconstruction. Due to the high-grade histology and resource constraints preventing dynamic sentinel node biopsy, the patient was managed with a strict active surveillance protocol for the inguinal basin. Histopathology using Hematoxylin and Eosin (H&E) staining confirmed a high-grade malignancy with a predominant population of atypical spindle cells arranged in fascicles, consistent with Spindle Cell Carcinoma. Deep and lateral margins were negative. At 12-month follow-up, the patient remains disease-free with no evidence of local recurrence or inguinal lymphadenopathy. The International Index of Erectile Function (IIEF-5) score remained stable (23/25), indicating excellent functional preservation. In conclusion, penile preservation via WLE is a viable option for selected cases of Spindle Cell Carcinoma. In resource-limited settings where immunohistochemistry is inaccessible, accurate diagnosis relies on identifying characteristic morphological features on H&E staining combined with clinical history. Strict surveillance is mandatory to monitor for nodal progression in the absence of invasive staging.